(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the profound influence of society on the protagonist, Pip, in Charles Dickens’ “Great Expectations”. As an orphan growing up in 19th-century England, Pip’s life is shaped by rigid class structures, societal expectations, and relationships with individuals who embody various societal values. The discussion examines key moments and remarks from the novel where societal pressures and aspirations for upward mobility shape Pip’s identity and decisions. This article highlights how Dickens critiques Victorian society’s obsession with class and wealth while portraying Pip’s eventual moral redemption.